Carpentry and building construction - Feirer, John L.; Hutchings, Gilbert R. (USA : Glencoe, 1986)
Introduction. Materials. Tools and machines. Foundations. Framing. Completing the exterior. Completing the interior. Special construction activities. Related activities.
Keywords: Construction; Building; Carpentry; Carpentry and building -- Construction